Investigation of Shape Memory Behavior in Cu-Based Quaternary Shape Memory Alloys - Unlu, N.; Ozkul, I.; Canbay, C. Aksu (Amer Inst Physics, 2018)
In Cu-based shape memory alloys, martensitic transformations occur regularly from the bcc beta phase. At high temperature, the irregular beta-phase cooling results in a regular transformation of the short-haul cycle and the B2 superstructure. The nearest neighboring structure is formed by cooling and the DO3 structure or the L2(1) superplastic structure is formed depending on the cooling rate for the structure alloy composition. In practice, it is known that many alloys have shape recalling effect. Among these alloys, most NiTi and Cu-based alloys are of interest. Although Cu-based alloys are susceptible to corrosion, the research on Cu-based alloys has gained intense due to their ease of manufacture and low cost compared to NiTi alloys. Machining equipment and construction tools are particularly preferred areas for shape recall alloys. In addition, biomedical, aviation and many other areas are used.
34th International Physics Congress (IPS) of the Turkish-Physical-Society (TPS) -- SEP 05-09, 2018 -- Konacik, TURKEY
Keywords: Quaternary SMA; thermal analysis; structural analysis